Halide solid electrolyte, preparation method thereof and all-solid-state battery
By using LI (2+X) ZRCL (6-X) SX structured halide solid electrolyte, it is prepared through high-energy ball mills to solve the problem of low conductivity and cost of the existing halide solid electrolyte ion ion. The electrolyte performance of cost is suitable for the application of a full solid -state battery.
Patent Information
- Application Number
- CN202411209467.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-24
AI Technical Summary
The existing halide solid electrolytes have low ionic conductivity and doping high-valent metal ions leads to increased costs.
The halide solid electrolytes that are composed of Li (2+X) ZRCL (6-X) SX are prepared by high-energy ball grinding for lithium chloride, chloride, lithium sulfide in an inert atmosphere to improve the electrolyte ion conduction rate Essence
A high -ionic conductivity, low -cost halide solid electrolyte, has high mechanical strength, wide -electrochemical chemical windows, and good electrochemical stability, and is suitable for the application of all -solid -state batteries.
Smart Images

Figure CN119361804A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a halide solid electrolyte and a preparation method thereof and an all-solid-state battery. Background Art
[0002] At present, halide solid electrolytes have attracted much attention due to their significant advantages, including: (1) they have good ionic conductivity, which means that they can effectively transfer ions and thus achieve efficient electrolyte functions; (2) due to the stability of the halide chemical composition, halide solid electrolytes generally have high chemical stability and can maintain their performance over a wide temperature range; (3) compared with liquid electrolytes, halide solid electrolytes are less volatile, which improves the safety of batteries and other electrochemical devices; (4) some halide solid electrolytes have good temperature stability, allowing batteries to operate effectively under different environmental conditions. However, the conductivity of the halide solid electrolytes currently studied is generally low.
[0003] CN117154201A discloses a solid electrolyte material doped with an inorganic nano hydrophobic material, and its preparation method and application. The solid electrolyte comprises solid electrolyte particles and inorganic nano hydrophobic materials physically doped in the solid electrolyte particles; the solid electrolyte particles are halide solid electrolytes and / or sulfide solid electrolytes; the particle size of the inorganic nano hydrophobic material is 1nm to 60nm. The chemical formula of the halide solid electrolyte is LiaMXb, and the M is selected from Mg2+, Al3+, Ga3+, In3+, Sb3+, Bi3+, Y3+, Sc3+, La3+, Ce3+, Pr3+, Nd3+, Pm3+, Sm3+, Eu3+, Gd3+, Tb3+, Dy3+, Ho3+, Er3+, Tm3+, Yb3+, Lu3+, Zr4+, Hf4+, Cr3+ , Fe3+, Zn2+ and Cd2+, X=at least one of Cl, Br, I and F, wherein 1≤a≤3, 1≤b≤5; preferably, M is at least one of Ga3+, In3+, Y3+, Sc3+, Ho3+, Yb3+, Lu3+, Zr4+ and Hf4+, and X is at least one of Cl and Br; the general chemical formula of the sulfide solid electrolyte is Li6PS5X, wherein X is a halogen.
[0004] CN 118054065 B discloses a self-supporting all-solid electrolyte membrane, characterized in that the self-supporting all-solid electrolyte membrane comprises a porous skeleton, a first solid electrolyte layer and a second solid electrolyte layer arranged on both sides of the porous skeleton, and a third solid electrolyte layer arranged on the surface of the first solid electrolyte layer away from the porous skeleton, the first solid electrolyte layer comprises a halide electrolyte, the second solid electrolyte layer comprises a high ion conductivity sulfide electrolyte, and the third solid electrolyte layer comprises a reduction-resistant sulfide electrolyte; the chemical formula of the halide electrolyte is LixMB6, M comprises Y, Zr, In, Sc, T a or La, any one or a combination of at least two, B includes Cl, Br or I, any one or a combination of at least two, 2≤x≤3, the high ion conductivity sulfide electrolyte includes Li10GeP2S12 and / or Li9.54Si1.74P1.44S11.7Cl0.3, the reduction-resistant sulfide electrolyte includes Li(6-x)PS(5-x)X(1+x) and / or yLi2S·(1-y)P2S5, wherein X includes Cl, Br or I, any one or a combination of at least two, 0≤x≤0.6, 0.2≤y≤0.8.
[0005] CN 116365017 A discloses a solid electrolyte composite material, characterized in that it comprises a lithium-containing solid electrolyte material, a stabilizer and an active additive; the lithium-containing solid electrolyte material is one or more of a sulfide solid electrolyte material, a halide electrolyte material and a NASICON phase oxide electrolyte material; the stabilizer is a high molecular polymer, including one or more of polyethylene terephthalate (PET), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), styrene-butadiene latex adhesive (SBR) and derivatives thereof; the active additive is a non-metallic halide, including at least one of POX3, PSX3, PNX2 and a mixture, composite and compound thereof; wherein X is one or more of F, Cl, Br and I. The sulfide solid electrolyte material includes: argyrodite Li6PS5Cl and its derivatives; lithium germanium phosphorus sulfur phase Li10MP2S12 and its derivatives, M = one or more of Si, Ge, Sn, Zn, Al; lithium phosphorus sulfur phase Li3PS4 phase or Li7P3S11 phase and its derivatives; Li4SiS4 phase and its derivatives; and / or, the halide electrolyte material is LiaMXb, M = one or more of Al, In, Ga, Y, Sc, La series rare earth elements, Nb, Ta, Zr, Hf, Fe, X is one or more of F, Cl, Br, I, 0.5≤a≤4, 3≤b≤8.
[0006] The above technical core focuses on the fields of sulfide electrolytes and halide electrolytes, focusing on exploring the influence of cation modification strategies and doping effects on electrolyte performance, and involving the structural design of halide and sulfide composite electrolytes. However, it is worth noting that there are no relevant reports on research cases of doping sulfur anions in halide electrolyte systems. Summary of the invention
[0007] The purpose of the present invention is to overcome the defects of the prior art electrolytes such as low ionic conductivity and increased cost due to doping with high-valent metal ions, and to provide a new type of halide solid electrolyte with the advantages of high ionic conductivity and low price. The application of the electrolyte in all-solid-state batteries provides a new idea for improving the energy density of all-solid-state lithium batteries, and also develops new ideas for all-solid-state lithium batteries.
[0008] According to a first aspect of the present invention, the present invention provides a halide solid electrolyte having Li (2+x) ZrCl (6-x) S x The composition of x is 0.25-2.
[0009] According to a second aspect of the present invention, the present invention provides a method for preparing the halide solid electrolyte described in the present invention, wherein the method comprises: subjecting lithium chloride, zirconium chloride and lithium sulfide to high-energy ball milling under an inert atmosphere.
[0010] According to a third aspect of the present invention, the present invention provides an all-solid-state battery, wherein the electrolyte of the all-solid-state battery comprises the halide solid electrolyte described in the present invention.
[0011] The solid electrolyte developed by the present invention has the advantages of high ion conductivity, high mechanical strength, wide electrochemical window, good electrochemical stability and low price. In the composite positive electrode, it can not only assist lithium ion transmission but also participate in charging and discharging to provide capacity. At the same time, the composite positive electrode material can have good contact with the electrolyte of the present invention. This material provides a new idea for improving the energy density of all-solid-state lithium batteries. At the same time, this new combination has developed new ideas for subsequent applications in all-solid-state lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is the first week charge and discharge diagram of the all-solid-state battery of Example 1.
[0013] Figure 2 This is the coulombic efficiency diagram of the all-solid-state battery of Example 1 in the first 13 weeks. DETAILED DESCRIPTION
[0014] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0015] The present invention provides a halide solid electrolyte, the solid electrolyte having Li (2+x) ZrCl (6-x) S x The composition of x is 0.25-2. The solid electrolyte developed by the present invention has the advantages of high ion conductivity, high mechanical strength, wide electrochemical window, good electrochemical stability and low price.
[0016] According to a preferred embodiment of the present invention, x is 0.25-0.75, such as 0.25, 0.35, 0.45, 0.55, 0.65, etc., preferably 0.25. The above preferred technical solution has the advantage of the highest ion conductivity.
[0017] According to a preferred embodiment of the present invention, the ionic conductivity of the solid electrolyte is (2-10)×10 -4 S cm -1 ; preferably (5-8)×10 -4 S cm -1 .
[0018] The halide solid electrolytes having the aforementioned characteristics of the present invention can achieve the purpose of the present invention, and there are no special requirements for their preparation methods. According to a preferred embodiment of the present invention, the present invention provides a preparation method of the halide solid electrolyte, wherein the method comprises: high-energy ball milling lithium chloride, zirconium chloride, and lithium sulfide under an inert atmosphere.
[0019] In the present invention, the conditions for high-energy ball milling can be selected in a wide range, which is exemplified below, but does not limit the scope of the present invention.
[0020] In the present invention, the ball-to-material ratio has a wide range of selectable ranges. According to one embodiment of the present invention, the ball-to-material mass ratio is 20-80: 1. The solid electrolyte obtained by adopting the above preferred ball-to-material ratio has the advantages of high ion conductivity, high mechanical strength, wide electrochemical window, good electrochemical stability and low price.
[0021] The present invention has no special requirements for the ball milling equipment. According to one embodiment of the present invention, the ball mill is a zirconia ball mill. The aforementioned preferred zirconia ball mill has the following advantages: (1) extremely high hardness, which can effectively grind and crush various materials; (2) very good wear resistance, long service life, and reduced pollution caused by the wear of the tank during the grinding process; (3) very good chemical stability, not easy to react or dissolve with the grinding material, can ensure the purity of the grinding process, and avoid contamination of the sample; (4) high mechanical strength and impact resistance, can withstand large impact force without being easily damaged, etc.
[0022] The present invention has no special requirements for the rotation speed of the ball mill, for example, the rotation speed is 450-550rpm / min, preferably 500-550rpm / min, for example, 520rpm / min, 530rpm / min, 540rpm / min, 550rpm / min, preferably 550rpm / min. The solid electrolyte obtained by the above rotation speed has the advantages of high ion conductivity, high mechanical strength, wide electrochemical window, good electrochemical stability and low price.
[0023] The present invention has no special requirements for the ball milling time. According to one embodiment of the present invention, the ball milling time is 32-48 hours, preferably 38-42 hours, for example, 39 hours, 40 hours, 41 hours, 42 hours, preferably 40 hours.
[0024] The present invention has no special requirements for the inert atmosphere. According to a preferred embodiment of the present invention, the inert atmosphere is an argon atmosphere.
[0025] According to a preferred embodiment of the present invention, low-speed ball milling premixing is performed before ball milling, and the premixing conditions include a speed of 100-300 rpm / min and a time of 5-20 min. The solid electrolyte obtained by the above method has the advantages of high ion conductivity, high mechanical strength, wide electrochemical window, good electrochemical stability and low price.
[0026] The present invention provides an all-solid-state battery, wherein the electrolyte of the all-solid-state battery comprises the halide solid electrolyte of the present invention. The all-solid-state battery using the halide solid electrolyte of the present invention has the advantages of high safety, long service life, and environmental friendliness.
[0027] The present invention has no special requirements for the battery structure, and commonly used battery structures can be applied to the present invention. According to a preferred embodiment of the present invention, the battery includes: a positive electrode, a negative electrode and an electrolyte layer located between the positive and negative electrodes, and the electrolyte layer includes an electrolyte protective layer and the halide solid electrolyte layer located between the electrolyte protective layers.
[0028] The present invention has no special requirements on the materials of the positive electrode, the negative electrode and the electrolyte protection layer. The following is an exemplary description, but the scope of the present invention is not limited thereby.
[0029] According to a preferred embodiment of the present invention, the electrolyte material of the electrolyte protection layer is one or more of the argyrodite-type materials Li6PS5Cl.
[0030] In the present invention, commonly used positive electrodes can achieve the purpose of the present invention, and there are no special requirements for the composition of the positive electrode active material layer of the positive electrode. It is worth mentioning that an electrolyte component is generally added to the positive electrode active material layer, and preferably the solid electrolyte described in the present invention is added. There are no special requirements for the positive electrode active material, conductive agent type and specific composition of the positive electrode active material layer.
[0031] According to a preferred embodiment of the present invention, the positive electrode material of the battery is a positive electrode composite material, which includes 28.5-66.7wt% of positive electrode active material, 0-5wt% of conductive agent, and 33.25-71.5wt% of electrolyte.
[0032] According to a preferred embodiment of the present invention, the electrolyte in the positive electrode is the solid electrolyte described above in the present invention.
[0033] The present invention has no special requirements on the type of positive electrode active material. This is an exemplary description, but it does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the positive electrode active material is one or more of NCM811 and lithium cobalt oxide.
[0034] The present invention has no special requirements on the type of conductive agent. It is only an exemplary description, but does not limit the scope of the present invention. According to a preferred embodiment of the present invention, the conductive agent includes one or more of acetylene black, carbon nanofibers, and carbon black.
[0035] In the present invention, the type of negative electrode of the all-solid-state lithium battery can be selected from a wide range, and commonly used negative electrode materials can be used in the present invention. An embodiment is illustrated by way of example, but the scope of the present invention is not limited thereby. For example, the negative electrode material of the battery includes a Li-In alloy, such as a Li sheet and / or an In sheet.
[0036] According to a particularly preferred embodiment of the present invention, preferably, the thickness of the Li sheet is 0.05 mm to 0.1 mm, and the thickness of the In sheet is 0.05 mm to 0.1 mm.
[0037] The present invention will be described in detail by way of examples. In the following examples, the ionic conductivity parameters are measured by a DC impedance method; the raw material lithium chloride for ball milling is a commercial product with a brand name of MJ10046-25g from Zancheng (Tianjin) Technology Co., Ltd., zirconium chloride is a commercial product with a brand name of Z70008-25g from Jiangsu Aikang Biopharmaceutical Research and Development Co., Ltd., and lithium sulfide is a commercial product with a brand name of YY85624-1g from Zancheng (Tianjin) Technology Co., Ltd.
[0038] Definition of effective ball milling time: The ball mill is set to a cycle of 20 minutes of rotation and 10 minutes of rest. The effective ball milling time is the sum of the rotation time, and the calculation method is: effective ball milling time = total time × 2 / 3.
[0039] The embodiment 1 of the present invention, in which x=0.25, ball milling time is 40h, ball milling speed is 550rpm / min, and ball-to-material ratio is 40:1, has significantly better effects such as higher ion conductivity and better dispersion effect.
[0040] Example 1
[0041] (1)Li 2.25 ZrCl 5.75 S 0.25 Preparation: Lithium chloride, zirconium chloride and lithium sulfide were weighed in proportion under an argon atmosphere and sealed in a zirconia ball mill. The ball-to-material ratio was 40:1. They were premixed at 200 rpm / min for 10 min, and then the ball mill speed was increased to 550 rpm / min. The effective ball milling time was 40 h. The ball-milled samples were collected. The ionic conductivity was 7.7×10 -4 S cm -1 ;
[0042] (2)Li 2.25 ZrCl 5.75 S 0.25 Preparation of composite positive electrode materials: weigh 60 mg of NCM811 positive electrode, 140 mg of Li 2.25 ZrCl 5.75 S 0.25 The electrolyte and 10 mg of Super P were put into a mortar and ground for 20 min, and the ground samples were collected.
[0043] (3) Preparation of all-solid-state battery: First, weigh 70 mg of protective layer electrolyte Li6PS5Cl and put it into a mold and press it with a force of 1.5 t for 1 minute; second, weigh 30 mg of Li prepared in step (1) 2.25 ZrCl 5.75 S 0.25 The electrolyte was placed in a mold and pressed with a force of 1.5 t for 1 minute; the third step was to weigh 6 mg of the Li prepared in step (2)2.25 ZrCl 5.75 S 0.25 The composite positive electrode material was pressed at a force of 4 tons for 3 minutes, and the positive electrode side was assembled; in the fourth step, a 0.1 mm thick indium sheet and a 0.1 mm thick lithium sheet were placed into the mold (the indium sheet was next to the Li6PS5Cl protective layer, and the lithium sheet was located below the indium sheet, and the rest of the embodiments were the same) and the negative electrode side was assembled into an all-solid-state battery. The all-solid-state battery was charged and discharged, and the charging capacity of the first cycle at an operating voltage of 1.9V-3.6V was 196.57mAh g -1 .
[0044] Figure 1 This is the first week charge and discharge diagram of the all-solid-state battery of Example 1. It shows that the synthesized solid electrolyte is well adapted to the NCM811 positive electrode material, the coulombic efficiency reaches 98.55%, the ion migration is good, and the solid electrolyte is successfully prepared;
[0045] Figure 2 This is the coulomb efficiency diagram of the all-solid-state battery of Example 1 in the first 13 weeks. The coulomb efficiency is above 95%, indicating that the ion migration inside the battery is good.
[0046] Example 2
[0047] (1)Li 2.55 ZrCl 5.45 S 0.55 Preparation: Lithium chloride, zirconium chloride and lithium sulfide were weighed in proportion under an argon atmosphere and sealed in a zirconia ball mill. The ball-to-material ratio was 20:1. They were premixed at 200 rpm / min for 10 minutes, and then the ball mill speed was increased to 550 rpm / min. The effective ball milling time was 40 hours. The ball-milled samples were collected, and the ionic conductivity was 2.91×10 -4 S cm -1 ;
[0048] (2)Li 2.55 ZrCl 5.45 S 0.55 Preparation of composite positive electrode materials: weigh 60 mg of NCM811 positive electrode, 140 mg of Li 2.55 ZrCl 5.45 S 0.55 The electrolyte and 10 mg of Super P were put into a mortar and ground for 20 min, and the ground samples were collected.
[0049] (3) Preparation of all-solid-state battery: First, weigh 70 mg of protective layer electrolyte Li6PS5Cl and put it into a mold and press it with a force of 1.5 t for 1 minute; second, weigh 30 mg of Li prepared in step (1) 2.55 ZrCl 5.45 S 0.55The electrolyte was placed in a mold and pressed with a force of 1.5 t for 1 minute; the third step was to weigh 6 mg of the Li prepared in step (2) 2.55 ZrCl 5.45 S 0.55 The composite positive electrode material was pressed with a force of 4 tons for 3 minutes to assemble the positive electrode side. In the fourth step, a 0.1mm thick indium sheet and a 0.1mm thick lithium sheet were placed on the negative electrode side of the mold to assemble the all-solid-state battery. The all-solid-state battery was tested for charge and discharge. The charge capacity of the first cycle was 175.67mAh g at an operating voltage of 1.9V-3.6V. -1 .
[0050] Example 3
[0051] (1)Li 2.75 ZrCl 5.25 S 0.75 Preparation: Lithium chloride, zirconium chloride and lithium sulfide were weighed in proportion under an argon atmosphere and sealed in a zirconia ball mill with a ball-to-material ratio of 80:1. They were premixed at 200 rpm / min for 10 minutes, and then the ball mill speed was increased to 550 rpm / min. The effective ball milling time was 40 hours. The ball-milled samples were collected, and the ionic conductivity was 5.5×10 -4 S cm -1 ;
[0052] (2)Li 2.75 ZrCl 5.25 S 0.75 Preparation of composite positive electrode materials: weigh 60 mg of NCM811 positive electrode, 140 mg of Li 2.75 ZrCl 5.25 S 0.75 The electrolyte and 10 mg of Super P were put into a mortar and ground for 20 min, and the ground samples were collected.
[0053] (3) Preparation of all-solid-state battery: First, weigh 70 mg of protective layer electrolyte Li6PS5Cl and put it into a mold and press it with a force of 1.5 t for 1 minute; second, weigh 30 mg of Li prepared in step (1) 2.75 ZrCl 5.25 S 0.75 The electrolyte was placed in a mold and pressed with a force of 1.5 t for 1 minute; the third step was to weigh 6 mg of the Li prepared in step (2) 2.75 ZrCl 5.25 S 0.75The composite positive electrode material was pressed with a force of 4 tons for 3 minutes to assemble the positive electrode side. In the fourth step, a 0.1mm thick indium sheet and a 0.1mm thick lithium sheet were placed on the negative electrode side of the mold to assemble the all-solid-state battery. The all-solid-state battery was tested for charge and discharge. The charge capacity of the first cycle was 170.78mAh g at an operating voltage of 1.9V-3.6V. -1 .
[0054] Example 4
[0055] According to the method of Example 1, other processes in the experiment were unchanged, only the ball milling speed was reduced to 500 rpm / min, and the other conditions were the same. The ionic conductivity of the solid electrolyte was 5.5×10 -4 S cm -1 .
[0056] The all-solid-state battery was charged and discharged. The charging capacity of the first cycle was 171.2 mAh g at an operating voltage of 1.9 V to 3.6 V. -1 .
[0057] Comparative Example 1
[0058] The method of Example 1 is followed, except that lithium sulfide is not introduced, and the prepared solid electrolyte is Li2ZrCl6, with an ionic conductivity of 1.20×10 -4 S cm -1 , it can be seen that the ionic conductivity of the solid electrolyte doped with S element is greatly improved.
[0059] The all-solid-state battery was charged and discharged. The charging capacity of the first cycle was 150.9 mAh g at an operating voltage of 1.9 V to 3.6 V. -1 .
[0060] Comparative Example 2
[0061] According to the method of Example 1, a solid electrolyte Li 2.1 ZrCl 5.9 S 0.1 , the ionic conductivity is 1.50×10 -4 Scm -1 .
[0062] The all-solid-state battery was charged and discharged. The charging capacity of the first cycle was 146.8 mAh g at an operating voltage of 1.9 V to 3.6 V. -1 .
[0063] Comparative Example 3
[0064] According to the method of Example 1, a solid electrolyte Li5ZrCl3S3 was prepared, and the ionic conductivity was 0.30×10 -6 S cm-1 .
[0065] The all-solid-state battery was charged and discharged. The charging capacity in the first cycle was 58.7 mAh g at an operating voltage of 1.9 V to 3.6 V. -1 .
[0066] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A halide solid electrolyte, characterized in that: The solid electrolyte has Li (2+x) ZrCl (6-x) S x The composition of x is 0.25-2.
2. The solid electrolyte according to claim 1, wherein x is 0.25-0.
75.
3. The solid electrolyte according to claim 1 or 2, wherein: The ionic conductivity of the solid electrolyte is (2-10)×10 -4 S cm -1 ; preferably (5-8)×10 -4 S cm -1 .
4. The method for preparing the halide solid electrolyte according to any one of claims 1 to 3, wherein: The method comprises: performing high-energy ball milling on lithium chloride, zirconium chloride and lithium sulfide under an inert atmosphere.
5. The preparation method according to claim 4, wherein The conditions for high energy ball milling include: The ball-to-material mass ratio is 20-80:1; The ball mill is a zirconia ball mill; The rotation speed is 450-550rpm / min, preferably 500-550rpm / min; The ball milling time is 32-48h, preferably 38-42h; The inert atmosphere is argon atmosphere; Preferably, low-speed ball milling premixing is performed before ball milling, and the premixing conditions include a speed of 100-300 rpm / min and a time of 5-20 min.
6. An all-solid-state battery, characterized in that: The electrolyte of the all-solid-state battery comprises the halide solid electrolyte described in any one of claims 1 to 3.
7. The battery according to claim 6, wherein The battery comprises: a positive electrode, a negative electrode and an electrolyte layer located between the positive electrode and the negative electrode, wherein the electrolyte layer comprises an electrolyte protection layer and the halide solid electrolyte layer located between the electrolyte protection layers.
8. The battery according to claim 7, wherein The electrolyte material of the electrolyte protection layer is argyrodite-type material Li6PS5Cl.
9. The battery according to any one of claims 6 to 8, wherein: The positive electrode material of the battery is a positive electrode composite material, which includes 28.5-66.7wt% of a positive electrode active material, 0-5wt% of a conductive agent, and 33.25-71.5wt% of an electrolyte; in, The electrolyte is the electrolyte according to any one of claims 1 to 3; The positive electrode active material is one or more of NCM811 and lithium cobalt oxide; The conductive agent includes one or more of acetylene black, carbon nanofiber, and carbon black.
10. The battery according to any one of claims 6 to 8, wherein: The negative electrode material of the battery includes a Li sheet and / or an In sheet; Preferably, the thickness of the Li sheet is 0.05 mm to 0.1 mm, and the thickness of the In sheet is 0.05 mm to 0.1 mm.
Citation Information
Patent Citations
Halide all-solid-state battery material and preparation method and application thereof
CN115275331A
Halide solid electrolyte material and preparation method and application thereof
CN115377484A
Solid electrolyte and preparation method thereof, and all-solid-state battery and manufacturing method thereof
CN115548427A
Solid electrolyte material and preparation method and application thereof
CN115676883A
A composition for preventing or treating hair loss comprising marliolide derivatives
KR1020200126505A
Cited By
Halide electrolyte electrode material, composite positive electrode, all-solid-state battery and manufacturing method of all-solid-state battery
CN120767328A